The electrochemical stability of ionic liquids and deep eutectic solvents - Li, Qingbo; Jiang, Jingyun; Li, Guofeng; Zhao, Wancheng; Zhao, Xinhui; Mu, Tiancheng (Science China. Chemistry, 2016)
Room temperature ionic liquids （ILs） composed of cations and anions, as well as deep eutectic solvents （DESs） composed of hydrogen bond donors （HBDs） and hydrogen bond acceptors （HBAs）, are regarded as green solvents due to their low volatility. They have been used widely for electrochemically driven reactions because they exhibit high conductivity and excellent elec- trochemical stability. However, no systematic investigations on the electrochemical potential windows （EPWs）, which could be used to characterize the electrochemical stability, have been reported. In this regard, the EPWs of 33 ILs and 23 DESs have been studied utilizing cyclic voltammetry （CV） method and the effects of structural factors （cations and anions of ILs, and HBDs and HBAs of DESs） and external factors （electrode, water content） on the EPWs have been comprehensively investi- gated. The electrochemical stability of selected 1Ls comprising five traditional cations, namely imidazolium, pyridinium, pyr- rolidinium, piperidinium and ammonium and 13 kinds of versatile anions was studied. The results show that for ILs, both cati- on and anion play an important role on the reductive and oxidative potential limit. For a same IL at different working electrode, for example, glassy carbon （GC）, gold （Au） and platinum （Pt） electrode, the largest potential window is almost observed on the GC working electrode. The investigations on the EPWs of choline chloride （ChCl）, choline bromide （ChBr）, choline iodide （ChI）, and methyl urea based DESs show that the DES composed of ChCl and methyl urea has the largest potential window. This work may aid the selection of ILs or DESs for use as a direct electrolyte or a solvent in electrochemical applications.